Estimating HIV incidence and assessing associated risk factors among adults: Evidence from the 2018–2022 HIV vaccine preparedness cohort in Masaka, Uganda - Sylvia Kusemererwa; Sheila Kansiime; Gertrude Mutonyi; Ayoub Kakande; Shamim Nabukenya; Aeron Namirembe; Naphtal Erima; Doreen Joan Asio; Elizabeth Mbabazi Atuhura; Shamim Ssendagire; Martin Onyango; Julie Fox; et al. (PLoS ONE, 2026)
Introduction Despite global reports of declining HIV incidence, current data are limited. This study presents findings on HIV incidence and risk factors in a HIV trial preparedness cohort. Methods Between 18 July 2018 and 13 October 2022, individuals 18–45-year-old were recruited from communities along the trans-African highway and the shores of Lake Victoria in Masaka district, Uganda. Eligible individuals were HIV-negative and met at least one of the following criteria: suspected or confirmed sexually transmitted infection (STI), unprotected sex with ≥2 partners, unprotected sex with a new partner in the past 3 months, or unprotected sex in exchange for money/goods in the past month. Baseline data included demographics, sexual behaviour, and HIV risk factors. Follow-up assessments of HIV risk and sexual behaviour were conducted every six months, while HIV counselling and testing (HCT) were provided every 3 months, with linkage to care for those testing positive. Data were summarised descriptively, and associations with HIV incidence were analysed using uni-variable and multi-variable Poisson regression models. Results Of the 1422 individuals enrolled, 1115 (78.4%) attended ≥1 follow-up visit; 69% were female and 55% were aged ≤24 years. Over 900.3 person-years of observation (PYO), 24 individuals acquired HIV, yielding an incidence rate (IR) of 2.7 PYO [95% Confidence Interval (CI): 1.8–4.0]. Baseline factors independently associated with incident HIV included female sex [adjusted incidence rate ratio (aIRR) = 6.84 PYO, 95% CI 1.60–29.30], residence in a fishing community [aIRR = 3.04 PYO, 95% CI 1.05–8.78] and recreational drug use in the past 3 months [aIRR = 3.08 PYO, 95% CI 1.19–7.99]. In a separate analysis, using time-updated variables assessed during follow-up, HIV acquisition was associated with sex after alcohol consumption [aIRR = 2.65 PYO, 95% CI 1.11–6.31], and STI diagnosis/treatment within the past 3 months [aIRR = 2.52 PYO, 95% CI 1.09–5.80]. Conclusion HIV incidence remains high among women, fishing community residents, and individuals with high risk behaviours, underscoring the need for targeted interventions to reduce the burden in these populations.